A COMPARATIVE ANALYSIS OF TWO LATEST NATIONAL EXAMINATION (UN) POLICY - Meli Aulia Utami; Riri Rachmah Riani; Nida Husna; Didin Nuruddin Hidayat (Universitas Sembilanbelas November Kolaka, 2021)
This study aims to compare the policy of the 2005-2013 National Examination (UN, hereafter) version with the latest one 2014-now. The implementation of later UN has received considerable critics. Now that the recent UN has upgraded the policy, we will see if the problems or critics found in the previous UN are solved in the latest one. By reviewing the UN's obstacles and controversy in later versions, we compare this with the current policy regulation. By employing library research, the present study identifies the controversy of later UN from various areas and years. The study revealed that the contemporary laws now solve the previously concerning reason to review UN policy. Further, the study also uncovered that the breakthrough of the new UN policy was on the content of the test. Another major findings derived from this study is that the application of the computer-based test reduced the possibility of the test takers to do cheating.